VALIDITAS MEDIA PEMBELAJARAN E-MODUL ACCURATE PADA MATA PELAJARAN KOMPUTER AKUNTANSI - Purba, Restina; Sibarani, Choms Gary Ganda Tua; Br.Sitanggang, Cindy Milasari; Simalango, Meylin (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
This study focuses on the development of an interactive E-Module based on the Accurate application as a learning medium for Accounting Computer subjects in vocational high schools. The research was motivated by the need of eleventh-grade Accounting students at SMKN 7 Medan for practical and efficient self-learning resources to better understand the preparation of digital financial statements using Accurate 5, considering the limitations of conventional learning media available at the school. The research employed the Research and Development (R&D) method by adopting the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The final product, an E-Module, is equipped with various interactive features such as material presentations with illustrations, instructional videos, real case examples, and practice exercises. The validation results indicated a very high level of feasibility, with a score of 90% from media experts and 92% from material experts, thus categorized as highly valid. The findings highlight that the Accurate E-Module is feasible to be used as an independent learning medium aligned with the student-centered learning approach in the Merdeka Curriculum. Therefore, this product offers an innovative solution for both teachers and students in addressing the challenges of accounting learning in the digital era.